问题 解答题
计算:(能简算的要简算)
4
9
÷(
5
6
-
1
2
)×(
7
8
-
1
2

②9
5
6
×4.25+4
1
4
×
1
6

3
4
-0.6×(2
5
12
-1.75)
④(6
1
2
-3
3
4
)÷(13+11
1
5

1
1×2
+
1
2×3
+
1
3×4
+
1
4×5
+…+
1
98×99
+
1
99×100

⑥3÷
1
3
÷
3
4
÷4.
答案

4
9
÷(
5
6
-
1
2
)×(
7
8
-
1
2
),

=

4
9
÷
1
3
×
3
8

=

4
3
×
3
8

=

1
2

②9

5
6
×4.25+4
1
4
×
1
6

=9

5
6
×4
1
4
+4
1
4
×
1
6

=4

1
4
×(9
5
6
+
1
6
),

=

17
4
×10,

=

85
2

3
4
-0.6×(2
5
12
-1.75),

=

3
4
-
3
5
×(2
5
12
-1
3
4
),

=

3
4
-
3
5
×
8
12

=

3
4
-
2
5

=

7
20

④(6

1
2
-3
3
4
)÷(13+11
1
5
),

=(

26
4
-
15
4
)÷(
65
5
+
56
5
),

=

11
4
÷
121
5

=

11
4
×
5
121

=

5
44

1
1×2
+
1
2×3
+
1
3×4
+
1
4×5
+…+
1
98×99
+
1
99×100

=(1-

1
2
)+(
1
2
-
1
3
)+(
1
3
-
1
4
)+…+(
1
98
-
1
99
)+(
1
99
-
1
100
),

=1-

1
2
+
1
2
-
1
3
+
1
3
-
1
4
+…+
1
98
-
1
99
+
1
99
-
1
100

=1-

1
100

=

99
100

⑥3÷

1
3
÷
3
4
÷4,

=3×3×

4
3
×
1
4

=3.

单项选择题
单项选择题